598. EPIPHRENIC DIVERTICULUM CAUSING GASTROESOPHAGEAL JUNCTION OUTFLOW OBSTRUCTION (EGJOO). (24th September 2022) - Lee, June; Lim, Annabelle; Lim, Xin Yan
Abstract: Oesophageal diverticulum is a rare cause of dysphagia. They are classified based on location- Zenker's diverticulum distal to the cricopharyngeus; epiphrenic diverticulum above the lower oesophageal sphincter (LES)- or pathophysiology – traction vs pulsion. The prevalence of epiphrenic pulsion diverticulum ranges from 0.2% to 0.8%. We present a case of epiphrenic diverticulum and its management. A 68 year old lady presents with dysphagia to solids and liquids, belching, food regurgitation, and acid brash for 10 years. She had no loss of weight, but experienced daily regurgitation and occasional retrosternal pain. Physical examination was unremarkable. We worked her up with further investigations and scans. A CT abdomen reported a hiatus hernia and mural thickening of distal oesophagus with upstream oesophageal distension. A oesophagogastroduodenoscopy showed residual food in oesophagus. The lower oesophagus was dilated and the LES appeared tight with no masses. There was no hiatus hernia on endoscopy. Barium swallow revealed the lower oesophageal dilatation to be an epiphrenic diverticulum. Manometry studies showed oesophago-gastric junction outflow obstruction. She underwent laparoscopic excision of esophageal diverticulum, cardiomyotomy and anterior partial fundoplication. The video serves to highlight the surgical key steps. She was discharged on post-operative day 3 without complications and barium swallow pre/post op as shown. Oesophageal diverticulum, although rare, remains a differential for dysphagia. For epiphrenic diverticulum, it is important to understand that this is a pulsion diverticulum, with an accompanying gastro-oesophageal outflow obstruction. In addition to surgical management with a laparoscopic diverticulectomy, a cardiomyotomy and partial fundoplication to treat underlying motility disorder is important. This case study and video serves to highlight the condition and present minimally invasive surgical management.